Synthesis and Characterization Superabsorbent Hydrogels of Partially Neutralized Acrylic Acid Prepared Using Gamma Irradiation; Swelling and Thermal Behavior - Erizal Erizal; Basril Abbas; Sulistioso Giat Sukaryo; Dhena Ria Barleany (Universitas Gadjah Mada, 2015)
A series of superabsorbent hydrogels were synthesized from partially neutralized acrylic acid with varying degree of neutralization (0-1) using gamma radiation. The effects of degree neutralization of acrylic acid on swelling ratio were studied. DSC measurement was performed to understand the type of end products resulting from irradiation. The morphologies of the hydrogels were examined using SEM. The chemical changes of the hydrogels were characterized using FTIR. At optimum conditions (10 kGy, 15 min), the hydrogels with neutralization degree 0.5 exhibited rapid swelling with the highest swelling ratio 1000 g/g. The results of DSC studies confirmed the possible formation of the type hydrogels from irradiated partially neutralized acrylic acid, and the hydrogels showed large numbers of pores from SEM examination.